Location-Based Analyses for Electronic Monitoring of Parolees - BIÇAKÇI, YUNUS SERHAT (MDPI, 2020)
This study analyses the spatio-temporal pattern of parolees using electronic monitoring, where the developed spatial framework supports the Environmental Criminology concepts such as crime patterns or crime attractive locations. A grid-based solution for spatio-temporal analyses is introduced to ensure the anonymity of the parolees. In order to test these developed concepts, the Istanbul Metropolitan Area was selected as the pilot study area. Following the developed concepts of the Crime Pattern Theory, a spatial framework was designed. A novel grid-based weighted algorithm for the most attractive areas was generated via spatial point-of-interest data and a conducted survey among police officers. The designed framework and the spatio-temporal analyses were carried out for 77 parolees using geostatistical methods. The major findings of the study are (a) 24-hour trajectories of each parolee was monitored; (b) the most attractive grids within the city were defined; and (c) for each parolee, the entrance time to the grid and the time spent within that grid were reported and analyzed. This study is a preliminary study for spatio-temporal detection of parolees' trajectories, where location-based analyses serve well. This study aims to aid decision-makers to better monitor the parolees and justify the benefits of surveillance.
Keywords: electronic monitoring; spatial; temporal; geographic information systems (GIS); R programming; Istanbul; SPATIAL EXTENT; CRIME; PATTERNS